WHOLE EXOME SEQUENCING OF A MULTIPLEX CROHN'S DISEASE FAMILY IDENTIFIES RARE ALTERATIONS IN PYGB ANDXRN2 AS POTENTIALLY HIGH IMPACT RISK VARIANTS OF DISEASE. (26th January 2023) - Chen, Lea Ann; Kim, Minsuk; Li, Dalin; Aita, Rohit; Cataldo, Susan; Radin, Arielle; Baylor, Jessica; Deng, Lily; Hahn, Brett; Wong, Kevin; Tin, Kevin; Mengesha, Emebet; et al.
Abstract: BACKGROUND: The study of multiplex Crohn's disease (CD) families has played a critical role in our understanding of the disease, including the identification of the first recognized CD risk variants in NOD2, which remain among the highest impact genetic predispositions known. Since then, genome wide association studies have revealed over 200 additional inflammatory bowel disease (IBD) risk alleles. However, such technologies may miss low prevalence, high impact variants. We therefore have been studying multiplex CD families to identify additional novel variants of disease. METHODS: A 3 generation family, including 5 CD subjects, 12 relatives, and 5 controls (spouses) underwent whole exome sequencing on the Illumina platform. Single nucleotide polymorphisms (SNPs) were identified, whose minor allele frequencies were <0.1% in all gnomAD subpopulations and were also predicted to be damaging, deleterious, or disease-causing by at least one of the pathogenicity prediction tools (PhyloP, SIFT, PolyPhen2, MutationTaster, LRT, and CADD). We selected the 5 CD diagnosed individuals, as well as a first degree relative of all 5 individuals (but who did not have CD) as the putative variant-carrying group. SNPs that were carried in this group, but were not found in the controls, were identified. Subjects for whom we did not have sufficient DNA to complete whole exome sequencing were excluded from analysis (Figure 1). RESULTS: We found 32 rare, pathogenic SNPs shared among the variant-carrying group. After removing those that were also found in any of the 5 controls, we were left with 4 variants as described in Table 1. Of these, rs145974526 was also found in 3 non-CD relatives (1 adult and 2 children). rs369261067 was also identified in 3 non-CD relatives (2 adults and 1 child). The remaining two variants (rs150582502 and rs149199982) were present in only 1 additional relative, the adult offspring of a CD-affected subject. Both SNPs are found on chromosome 20, and these risk alleles are located in the PYGB and XRN2 genes, respectively. Of note, NOD2 variants were not identified in this family. DISCUSSION: Based on our analysis, we identify SNPs rs150582502 and rs149199982 as possible private, rare, high impact variants for Crohn's disease. PYGB (glycogen phosphorylase B) has been shown to promote cellular proliferation in multiple tumor types by regulation of the Wnt/β-Catenin pathway. XRN2 encodes 5'-3' exoribonuclease 2, which is involved in transcription termination. Studies of XRN2 have demonstrated its involvement in DNA repair, and alterations in the gene have been identified in various cancers. Additional functional work will be performed to further validate the role of these mutations. We are also in the process of analyzing additional multiplex IBD families and datasets for these SNPs, as well as for other potential novel variants of disease.